Bis(acetonitrile-κN)(1,10-phenanthroline-κ(2) N,N′)platinum(II) bis(perchlorate) - Ha, Kwang (International Union of Crystallography, 2010)
The asymmetric unit of the title compound, [Pt(CH(3)CN)(2)(C(12)H(8)N(2))](ClO(4))(2), contains one half of a cationic Pt(II) complex and pair of half perchlorate anions, one of which is disordered over two sites in a 0.53 (3):0.47 (3) ratio. The complex and anions are disposed about a crystallographic mirror plane parallel to the ac plane passing through the Pt and Cl atoms. In the complex, the Pt(II) ion lies in a distorted square-planar environment defined by four N atoms of the chelating 1,10-phenanthroline ligand and two distinct acetonitrile molecules. The component ions interact by means of intermolecular C—H⋯O hydrogen bonds.